The Public Commodities Problem - Karl Widerquist (Levy Economics Institute of Bard College, 2000)
The decision about how much to spend on a public program depends on the answers to two questions: (1) a normative and binary question-Should the government pursue the goal of this program? (2) a positive and continuous question-Given that the program's goal should be adopted, what is the optimal level of spending to achieve it? If the answer to the first question is yes, it might seem desirable to set spending at the optimal level to achieve the goal; however, spending is often not set at that level and there is likely to be an underfunding bias. This paper uses the median voter theorem to demonstrate that the level that is approved does not depend solely on the amount supporters think is necessary. Opponents of the program's goal and supporters of the goal who favor relatively less spending than other supporters favor may form a coalition that ensures that the level of spending approved will be lower than the level most supporters think is optimal. The more opponents there are and the more disagreement there is among supporters about the optimal level, the greater the difference between the actual level of spending and the amount the typical supporter believes is optimal.
Keywords: 330